Pervious concrete design method capable of fully utilizing material performance

By calculating the minimum slurry thickness, minimum aggregate strength and minimum slurry strength of permeable concrete, the problem of insufficient material performance utilization in the existing design methods is solved, and efficient material utilization and engineering performance optimization are achieved.

CN119517247AInactive Publication Date: 2025-02-25GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411565423.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing permeable concrete design methods fail to fully utilize the material properties, resulting in mismatch between the strength properties of the aggregate and the slurry, resulting in waste of material utilization.

Method used

By determining the minimum slurry thickness, minimum aggregate strength and minimum slurry strength required for permeable concrete, combined with the relationship between aggregate particle size and slurry thickness, an appropriate material mix ratio is calculated to maximize the utilization of material performance.

Benefits of technology

It has achieved efficient utilization of permeable concrete, met the permeable performance and strength requirements, reduced engineering production costs, and promoted the green and low-carbon development of civil engineering materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517247A_ABST
    Figure CN119517247A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a pervious concrete design method capable of fully utilizing material performance. According to the method, the minimum slurry thickness, the minimum aggregate strength and the minimum slurry strength of the pervious concrete can be rapidly calculated according to the actually measured radius, the designed permeability coefficient and the designed compressive strength of the aggregate, the minimum slurry thickness, the minimum aggregate strength and the minimum slurry strength serve as control indexes of pervious concrete production, then the mixing ratio dosage is calculated, and materials with matched performance are selected. Therefore, the pervious concrete which meets the requirements of water permeability and strength performance and can fully utilize the material performance is obtained. The method overcomes the defects that performance utilization of the pervious concrete aggregate and the slurry material is not matched and material performance utilization is wasted in an existing design method, and material parameterization indexes are provided for pervious concrete industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a permeable concrete design method capable of fully utilizing material properties. Background Art

[0002] Permeable concrete is a porous material whose pore structure allows water to quickly penetrate and drain downward from the surface. It is often used in road paving and wetland revetments for ecological restoration. Permeable concrete is gradually becoming one of the important materials for improving the quality of urban infrastructure, solving ecological and environmental problems, realizing sponge city construction, and promoting sustainable development.

[0003] At present, the commonly used design methods for permeable concrete are "volume method", "specific surface area method" and "mass method". The volume method is to calculate the amount of each material based on the total volume of permeable concrete and the volume and density of each raw material; the specific surface area method is to measure or calculate the surface area of ​​the aggregate, and calculate the amount of each raw material based on the set slurry coating thickness; the mass method is to design and prepare permeable concrete based on the mass ratio of each component of permeable concrete. These mix design methods are all aimed at permeability, strength and other properties. Although the obtained mix ratio can meet the engineering design requirements, it is often found in engineering that the damage of permeable concrete is mostly caused by severe damage to one material, while other materials are very strong and remain intact. This is mainly because the current design method does not consider the problem of mutual matching of material properties and full utilization.

[0004] In the existing research, permeable concrete has failed to achieve the matching of aggregate particle size and slurry thickness under the premise of meeting the requirements of strength and permeability, and has failed to achieve the matching of aggregate and slurry strength performance. There is an obvious redundancy or insufficiency in the performance utilization of materials, resulting in waste of material utilization. The present invention attempts to provide a design method to solve the problem of insufficient performance utilization of existing permeable concrete materials, thereby achieving the goal of efficient utilization of materials and saving resources. Summary of the invention

[0005] The purpose of the present invention is to provide a permeable concrete design method that can fully utilize material properties. By determining the minimum slurry thickness, minimum aggregate strength and minimum slurry strength required for permeable concrete, a permeable concrete design method that can meet the permeability coefficient and strength requirements and maximize the utilization of material properties is obtained.

[0006] According to the engineering design requirements, by measuring the physical properties of the material, the method of the present invention can be used to calculate the minimum slurry thickness, minimum aggregate strength and minimum slurry strength, and then use these design parameters and controllable indicators to carry out permeable concrete slurry design and aggregate type selection. The present invention can provide parameterized indicators for aggregate particle size selection, minimum slurry thickness design, minimum slurry strength and aggregate strength index determination in the production process of permeable concrete.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a permeable concrete design method capable of fully utilizing material properties, the method comprising the following steps:

[0009] Step 1: Determine the design compressive strength σ of permeable concrete T and the design permeability coefficient k, and by the relationship P = 0.0539e 1.2181k The porosity P of permeable concrete is calculated.

[0010] Step 2: Calculate the minimum paste thickness t required for permeable concrete. The measured aggregate radius R and porosity P are used to calculate the minimum paste thickness t required for permeable concrete. The required minimum slurry thickness t is calculated; where α is the equivalent coefficient for porosity calculation, and single-grade aggregate is used. When the aggregate sizes are 3-5mm, 5-10mm, and 10-16mm, the values ​​of α are 4.5, 3.3, and 2.6, respectively.

[0011] Step 3: Calculate the minimum aggregate strength σ required for permeable concrete 骨 and minimum paste strength σ 浆 . The design strength of permeable concrete is σ T and the designed porosity P through the relationship Calculate and obtain the minimum aggregate strength σ 骨 ; Then by σ 骨 , R and t Calculate and obtain the minimum paste strength σ 浆 ; Wherein γ and μ are the equivalent coefficients of aggregate strength calculation and paste strength calculation and paste calculation radius, respectively, and the values ​​are γ=0.12 and μ=0.7.

[0012] Step 4: Calculation of the mix proportion of permeable concrete and selection of materials. Determine the size of the selected single-diameter aggregate and calculate the amount of aggregate based on the compact packing density of the aggregate; calculate the amount of slurry based on the aggregate surface area and the minimum slurry thickness t calculated in step 2. The mix proportion of permeable concrete can be determined based on the aggregate amount and slurry amount. Among them, the material selection should meet the actual measured strength σ of the selected aggregate 骨 'Not less than the minimum aggregate strength σ 骨, and under the principle of making full use of material properties, σ 骨 ' value should be close to σ 骨 The prepared cement paste 28d measured strength σ 浆 ' should not be less than the minimum paste strength σ 浆 , and under the principle of making full use of material properties, σ 浆 ' value should be close to σ 浆 Better.

[0013] The complete design process is as follows Figure 1 shown.

[0014] In step 1, the relationship between k and P is established by fitting experimental data (see Figure 2 ).

[0015] The calculation methods proposed in step 2 and step 3 are based on the following assumptions: the aggregate particles of permeable concrete are equivalent to ideal spheres and the paste is evenly coated (see Figure 3 ), and the aggregate is in the most densely packed cubic state.

[0016] In step 2, the aggregate radius R=2 / D; the aggregate diameter D is determined by the following method: randomly select i aggregates and measure the length D of the major axis i (i≥4), calculate the average diameter

[0017] In step 2, the relationship between porosity P, aggregate radius R, and slurry thickness t is established through the pore geometry relationship, specifically: in the plane single layer arrangement state, the total pore area S of the plane in the cube with a side length of a a The standard pore area S of u planes ps and v plane edge pore areas S pe Composed of; said u=2N c 2 (pcs), v = N c -1(pcs), then S a =2N c 2 S pa +(N c -1)S pe ; According to the relationship between the porosity of permeable concrete P = αS a / a 2 , then we get

[0018] The plane standard pore area S ps and R, t satisfy the geometric relationship (such as Figure 4 ): The plane edge pore area S pe Satisfies geometric relationship with R: Spe =0.4292R 2 ; said N c is the aggregate calculation number, N c Satisfies the relationship with R and a:

[0019] In summary, the relationship between the design porosity P of permeable concrete, the design radius R of aggregate, and the minimum paste thickness t can be obtained:

[0020] The coefficient α is the pore area equivalent coefficient, which is related to the aggregate particle size grade. When the single aggregate particle size grade is 3-5mm, 5-10mm, and 10-16mm, the values ​​of α are 4.5, 3.3, and 2.6, respectively.

[0021] The calculation method proposed in step 3 is based on the following assumptions: the permeable concrete is composed of several aggregate-paste-aggregate force-bearing units, and the magnitude of the force on each force-bearing unit is the same in the direction of the force; the aggregates of the force-bearing unit are connected by paste, and the force passes through the centroids of the two aggregates, and the paste "connector" is equivalent to a circular contact surface for calculation (such as Figure 5 ).

[0022] In step 3, σ 骨 With σ T , P is obtained by converting the strength formula; the conversion relationship is to convert the design compressive strength σ of permeable concrete under the action of the same axial force F T (cube with side length a) is converted to the aggregate stress per unit area minus the void area (i.e. the minimum aggregate strength σ 骨 ), specifically: 骨 (1-P)a 2 =F=σ T δa 2 ; The δ is the area conversion coefficient related to P, δ = 70.83P-1.9505; In summary, establish σ 骨 With σ T 、P:

[0023] In step 3, σ 浆 With σ 骨 The relationship is obtained by converting the strength formula under the principle of making full use of material properties; the principle is that when the permeable concrete reaches the ultimate compressive strength, the simultaneous destruction of aggregate and paste is regarded as the most fully utilized state of the material, that is, the aggregate and paste with different action areas must withstand the same axial force; the conversion relationship is obtained by converting the minimum aggregate strength σ by the strength formula under the action of the same axial force F' 骨Converted to the slurry strength related to R and t (i.e. the minimum slurry strength σ 浆 ), specifically: 浆 S 浆 =F' = σ 骨 S 骨 ; The S 骨 The effective cross-sectional area of ​​aggregate is: S 骨 =πR 2 ; The S 浆 is the effective calculated cross-sectional area of ​​the paste “connector” on the section perpendicular to the line connecting the centroids of the connected aggregates, specifically S 浆 =πr 2 ; The r is the radius of the slurry "connector", specifically: In summary, we establish σ 浆 With σ 骨 , R, t: Among them, γ and μ are equivalent coefficients, γ=0.12, μ=0.7.

[0024] In step 3, the actual aggregate strength σ 骨 'Strength testing is carried out according to the methods of "Quality and Inspection Standards of Sand and Stone for Ordinary Concrete" and "Pebble and Crushed Stone for Construction".

[0025] Furthermore, the minimum aggregate strength σ 骨 It can be used as the actual aggregate strength σ for permeable concrete production 骨 ' reference index, requiring σ 骨 '≥σ 骨 , and under the principle of fully utilizing material properties, σ 骨 ' value should be close to σ 骨 Better.

[0026] In step 4, the calculation method of the amount of aggregate and the amount of slurry is specifically as follows: Aggregate dosage (kg / m 3 ) = aggregate compact density (kg / m 3 )×0.98(reduction factor); The slurry dosage volume (m 3 ) = aggregate specific surface area (m 2 / kg)×aggregate dosage (kg / m 3 )×minimum slurry thickness t(mm)×10 -3 ; Said The m 骨1 is the mass of a single aggregate (kg), and three aggregates are randomly selected and weighed m i And take the average value,

[0027] In step 4, the compact packing density of the aggregate is measured according to the compact density test of crushed stone in the "Quality and Inspection Standards for Sand and Stone Used in Ordinary Concrete".

[0028] Based on the design requirements and basic material indicators, the minimum slurry thickness t and the minimum aggregate strength σ of permeable concrete can be calculated by the method of the present invention. 骨 and minimum paste strength σ 浆 By taking the above data as control indicators for slurry mixing and aggregate selection, permeable concrete can be formulated which can meet the requirements of permeability and strength and make full use of material properties.

[0029] The slurry described in the present invention is a cementitious material for bonding aggregates, and the components of the slurry include but are not limited to cement-based cementitious materials.

[0030] Compared with the existing method, the present invention has the following beneficial effects:

[0031] The method proposed in the present invention is based on the principle of full utilization of material properties. Starting from the law of aggregate arrangement and paste adhesion, it reveals the relationship between the pore area, aggregate and paste of permeable concrete, takes the aggregate radius, permeability coefficient and permeable concrete design strength as basic design parameters, calculates the minimum paste thickness, aggregate strength and paste strength and uses them as control indicators for permeable concrete production. This method makes up for the shortcomings of the existing design method of permeable concrete aggregate and paste material performance mismatch and waste of material performance utilization, and provides material design parameters for the industrial production of permeable concrete. In addition, the design method based on full utilization of material properties of the present invention can reduce engineering production costs, aiming to promote the green and low-carbon development of civil engineering materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A flow chart of the design method for permeable concrete that can fully utilize the material properties.

[0033] Figure 2 This is the relationship curve between permeability and porosity.

[0034] Figure 3 Schematic diagram of the equivalent aggregate-paste model of permeable concrete.

[0035] Figure 4 Schematic diagram of pore area relationship calculation.

[0036] Figure 5 Schematic diagram of the bone mortar force unit. DETAILED DESCRIPTION

[0037] The following examples are used to clearly and completely describe the present invention, but are not intended to limit the scope of the present invention.

[0038] In order to verify the effectiveness of the design process of the present invention, design calculations and experimental verifications were carried out for different aggregate particle size grades and engineering requirements. The specific implementation methods are shown in Examples 1 to 3.

[0039] Example 1

[0040] Design permeable concrete indicators to meet engineering design requirements: permeability coefficient k = 1mm / s, permeable concrete strength grade TC15 (28d compressive strength ≥ 15MPa).

[0041] Step 1, select aggregate with a particle size of 3-5mm, measure the actual parameter index of the aggregate, measure and calculate the aggregate to obtain D = 5mm, R = 2.5mm, α value α = 4.5; permeability k = 1mm / s, according to the formula P = 0.0539e 1.2181k The calculated design porosity P = 0.18; the strength grade TC15 is obtained as T =15MPa.

[0042] Step 2: According to the formula The calculated minimum slurry thickness is t=0.18 mm.

[0043] Step 3, according to the formula: Calculate the minimum aggregate strength σ 骨 =198MPa, minimum slurry strength σ 浆 =91MPa.

[0044] After design calculations, the design indicators of permeable concrete were obtained: minimum slurry thickness is 0.18mm, minimum aggregate strength is 198MPa, and minimum slurry strength is 91MPa.

[0045] Step 4: Calculate the amount of aggregate and paste required for preparing permeable concrete (see Table 1 for details), where the amount of paste is calculated based on the minimum paste thickness t obtained in step 2; select materials based on the minimum aggregate strength and minimum paste strength calculated in step 3. The actual aggregate selected is diabase, and the measured strength σ 骨 ' is 296MPa; the 28d measured strength of the selected cement paste σ 浆 ' is 105.5MPa (see Table 1 for slurry mix ratio).

[0046] The results of Example 1 are as follows: the measured 28d compressive strength of the permeable concrete is 18.2 MPa, and the water permeability coefficient is 1.13 mm / s, which meet the design requirements.

[0047] Example 2

[0048] The permeable concrete slurry is designed for aggregates with a particle size of 5-10mm to meet the engineering design requirements: permeability coefficient k=1mm / s, permeable concrete strength TC15.

[0049] Step 1, measure the actual parameter index of aggregate, measure and calculate the aggregate to get D = 9.6mm, R = 4.8mm, α = 3.3; permeability k = 1mm / s, according to the formula P = 0.0539e 1.2181k The calculated porosity P = 0.18; the σ is obtained from the strength grade TC15 T =15MPa.

[0050] Step 2: According to the formula The calculated minimum slurry thickness is t=0.4 mm.

[0051] Step 3, according to the formula: Calculate σ 骨 =182MPa,σ 浆 =73MPa.

[0052] After design calculations, the design indicators of permeable concrete were obtained: minimum slurry thickness is 0.4mm, minimum aggregate strength is 182MPa, and minimum slurry strength is 73MPa.

[0053] Step 4: Calculate the amount of aggregate and paste required for preparing permeable concrete (see Table 1 for details), where the amount of paste is calculated based on the minimum paste thickness t obtained in step 2; select materials based on the minimum aggregate strength and minimum paste strength calculated in step 3. The actual aggregate selected is diabase, and the measured strength σ 骨 ' is 296MPa; the 28d measured strength of the selected cement paste σ 浆 ' is 112.7MPa (see Table 1 for slurry mix ratio).

[0054] The results of Example 1 are as follows: the measured 28d compressive strength of the permeable concrete is 19.4 MPa, and the water permeability coefficient is 1.11 mm / s, which meet the design requirements.

[0055] Example 3

[0056] The permeable concrete slurry is designed for aggregates with a particle size of 10-15mm to meet the engineering design requirements: permeability coefficient k=1mm / s, permeable concrete strength TC20.

[0057] Step 1, measure the actual parameter index of aggregate, measure and calculate the aggregate to get D = 14.8mm, R = 7.4mm, α = 2.6; permeability k = 1mm / s, according to the formula P = 0.0539e 1.2181kThe calculated design porosity P = 0.18; the strength grade TC20 is obtained as σ T =20MPa.

[0058] Step 2: According to the formula The calculated minimum slurry thickness is t=0.6 mm.

[0059] Step 3, according to the formula: Calculate σ 骨 =263MPa,σ 浆 =107MPa.

[0060] After design calculations, the design indicators of permeable concrete were obtained: minimum slurry thickness is 0.6mm, minimum aggregate strength is 263MPa, and minimum slurry strength is 107MPa.

[0061] Step 4: Calculate the amount of aggregate and paste required for preparing permeable concrete (see Table 1 for details), where the amount of paste is calculated based on the minimum paste thickness t obtained in step 2; select materials based on the minimum aggregate strength and minimum paste strength calculated in step 3. The actual aggregate selected is diabase, and the measured strength σ 骨 ' is 296MPa; the 28d measured strength of the selected cement paste σ 浆 ' is 110MPa (see Table 1 for slurry mix ratio).

[0062] The results of Example 1 are as follows: the measured 28d compressive strength of the permeable concrete is 22.8 MPa, and the water permeability coefficient is 1.28 mm / s, which meet the design requirements.

[0063] In order to verify the effectiveness of the minimum slurry thickness t of the present invention and its utilization efficiency, Example 3 was used as a reference object (minimum slurry thickness t=0.6mm), and the situations of reducing the slurry thickness (t=0.5mm) and enlarging it (t=0.9mm) for preparing permeable concrete were compared. The specific implementation methods are shown in Comparative Examples 1 and 2.

[0064] Comparative Example 1

[0065] Except for the following technical features, the other technical features are the same as those in Example 3, the cement paste thickness is adjusted to t=0.5 mm, and the permeable concrete mix ratio is calculated according to step 4 as shown in Table 1;

[0066] The results of comparative example 1 are as follows: the measured 28d compressive strength of permeable concrete is 14.4MPa, and the permeability coefficient is 0.75, wherein the measured compressive strength is less than the design requirement of σ T =15MPa, does not meet the design requirements.

[0067] Comparative Example 2

[0068] Except for the following technical features, the other technical features are the same as those in Example 3, the cement paste thickness is adjusted to t=0.9 mm, and the permeable concrete mix ratio is calculated according to step 4 as shown in Table 1;

[0069] The results of comparative example 2 are as follows: the measured 28d compressive strength of the permeable concrete is 58.1MPa, and the water permeability coefficient is 0mm / s (slurry blocking holes), wherein the measured water permeability coefficient is less than the design requirement of k=1mm / s, and the water permeability does not meet the design requirements.

[0070] Examples 1 to 3 demonstrate the effectiveness of the present design method in meeting the design strength and permeability coefficient of permeable concrete. Comparative Examples 1 to 2 demonstrate the effectiveness of the minimum slurry thickness t in the present design method. When the slurry thickness is less than t, the concrete strength is insufficient; when the slurry thickness is greater than t, the permeability decreases.

[0071] Table 1 Raw material parameters and mix ratios of Examples 1 to 3 and Comparative Examples 1 to 2

[0072] In order to verify the minimum aggregate strength σ 骨 The effectiveness and utilization efficiency of Example 4 are taken as the basic design requirements and reference objects. The minimum aggregate strength (σ 骨 =146MPa), respectively using aggregate strength larger (σ 骨 '=296MPa) and the aggregate strength is too small (σ 骨 Different types of aggregates with a pressure of '=113MPa) are used to prepare permeable concrete and are compared. The specific implementation methods are shown in Example 4 and Comparative Examples 3 and 4.

[0073] Example 4

[0074] The permeable concrete slurry and aggregate indicators have a design strength of TC20 and a permeability coefficient of 0.9mm / s.

[0075] Step 1, measure the actual parameter index of aggregate, measure and calculate the aggregate to get D = 9.6mm, R = 4.8mm, α = 3.3; permeability k = 1mm / s, according to the formula P = 0.0539e 1.2181k The calculated design porosity P = 0.18; the strength grade TC20 is obtained as σ T =20MPa.

[0076] Step 2: According to the formula The minimum slurry thickness is calculated to be: t = 0.37 mm.

[0077] Step 3, according to the formula: Calculate σ骨 =146MPa,σ 浆 =63MPa.

[0078] Step 4: Calculate the amount of aggregate and paste required for preparing permeable concrete (see Table 2 for details), where the amount of paste is calculated based on the minimum paste thickness t obtained in step 2; select materials based on the minimum aggregate strength and minimum paste strength calculated in step 3. The actual aggregate selected is basalt, and the measured strength σ 骨 ' is 184MPa, not less than and close to the σ calculated in step 3 骨 =146MPa; 28d measured strength of the selected cement paste σ 浆 ' is 83.4MPa (see Table 2 for slurry mix ratio).

[0079] The results of Example 4 are as follows: the measured 28d compressive strength of the permeable concrete is 23.6MPa, and the water permeability coefficient is 0.99mm / s, which meet the design requirements; at the same time, the permeable concrete test block is a mixed failure of aggregate and slurry. It can be seen that when the strength of the aggregate selected in the design is close to the minimum aggregate, the strength of the aggregate can be fully utilized.

[0080] Comparative Example 3

[0081] Except for the following technical features, the other technical features are the same as those of Example 4; the strength of the aggregate used is improved, diabase is selected, and the actual measured compressive strength of the aggregate is 296 MPa. The specific formula is shown in Table 2.

[0082] The results of Comparative Example 3 are: the measured 28d compressive strength of permeable concrete is 35.1MPa, and the permeability coefficient is 1.1mm / s, which meets the design requirements. The measured strength is much higher than the design requirements, and the strength is redundant; the permeable concrete specimen is slurry-damaged, the aggregate is relatively intact, and the aggregate strength is not fully utilized, further indicating that the material performance is wasted.

[0083] Comparative Example 4

[0084] Except for the following technical features, the other technical features are the same as those of Example 4; the strength of the aggregate used is reduced, and granite is selected. The actual measured compressive strength of the aggregate is 113 MPa, and the specific formula is shown in Table 2.

[0085] The results of Comparative Example 4 are: the measured 28d compressive strength of the permeable concrete is 18.4MPa, the permeability coefficient is 1.33mm / s, and the strength index does not meet the design requirements; at the same time, it is found that the permeable concrete test block shows aggregate damage, indicating that the aggregate strength does not match the design strength of the permeable concrete, resulting in insufficient strength of the permeable concrete.

[0086] Example 4 further proves the effectiveness of this design method in meeting the design strength and permeability coefficient of permeable concrete, and proves that when the aggregate strength σ 骨' is greater than and close to the minimum aggregate strength σ calculated by this method 骨 When σ is equal to the strength of permeable concrete, the aggregate strength is fully utilized; Comparative Examples 3 and 4 show that the aggregate strength is greater than σ 骨 When the aggregate strength is less than σ 骨 This results in insufficient concrete strength.

[0087] Table 2 Raw material parameters and mix ratios of Example 4 and Comparative Examples 3 to 4

[0088] In order to verify the minimum slurry strength σ 浆 The effectiveness and utilization efficiency of Example 5 are taken as the basic design and reference object. The minimum slurry strength (σ 浆 =85MPa), the slurry strength is increased (σ 浆 '=113.2MPa) and the slurry strength decreases (σ 浆 '=83.4MPa) are used to prepare permeable concrete and compared. The specific implementation methods are shown in Example 5 and Comparative Examples 5 and 6.

[0089] Example 5

[0090] The permeable concrete slurry is designed for the existing aggregate with a particle size of 5-10mm to meet the engineering design requirements: permeability coefficient k=0.8mm / s, permeable concrete strength TC40.

[0091] Step 1, measure the actual parameter index of aggregate, measure and calculate the aggregate to get D = 8.4mm, R = 4.2mm, α = 3.3; permeability k = 0.8mm / s, according to the formula P = 0.0539e 1.2181k The calculated design porosity P = 0.15; the strength grade TC40 is obtained as σ T =40MPa.

[0092] Step 2: According to the formula The calculated minimum slurry thickness is t=0.37 mm.

[0093] Step 3, according to the formula: Calculate σ 骨 =227MPa,σ 浆 =85MPa.

[0094] Step 4: Calculate the amount of aggregate and paste required for preparing permeable concrete (see Table 3 for details), where the amount of paste is calculated based on the minimum paste thickness t obtained in step 2; select materials based on the minimum aggregate strength and minimum paste strength calculated in step 3. The actual aggregate selected is diabase, and the measured strength σ 骨 ' is 296MPa; the measured strength of the prepared cement paste at 28 days σ 浆 ' is 94.2MPa, which is not less than and close to the σ calculated in step 3 浆 =85MPa (see Table 3 for slurry mix ratio).

[0095] The results of Example 5 are as follows: the measured 28d compressive strength of the permeable concrete is 42.6 MPa, and the water permeability coefficient is 0.87 mm / s, which meet the design requirements; at the same time, the permeable concrete test block is a mixed failure of slurry and aggregate. It can be seen that when the slurry strength selected in the design is close to the minimum slurry strength, both the slurry and the aggregate are destroyed, and the strength of the slurry can be fully utilized.

[0096] Comparative Example 5

[0097] Except for the following technical features, the other technical features are the same as those in Example 5; the strength of the slurry used is adjusted and improved, and the measured slurry 28d compressive strength is 112.7MPa (the slurry mix ratio is shown in Table 3);

[0098] The results of Comparative Example 5 are: the measured 28d compressive strength of the permeable concrete is 43.5MPa, and the permeability coefficient is 0.81mm / s. Although the design requirements are met, the slurry strength of Comparative Example 5 is 20% higher than that of Example 6. However, the strength of the permeable concrete is only increased by 2%, which shows that the slurry material has not been effectively utilized. At the same time, it is found that the permeable concrete test block has aggregate damage and good slurry integrity, that is, the slurry strength fails to fully exert its effect, further indicating that increasing the slurry strength is relatively wasteful.

[0099] Comparative Example 6

[0100] Except for the following technical features, the other technical features are the same as those in Example 5; the strength of the slurry used is adjusted and reduced, and the measured slurry 28d compressive strength is 83.4MPa (the slurry mix ratio is shown in Table 3);

[0101] The results of Comparative Example 6 are as follows: the measured 28d compressive strength of the permeable concrete is 35.1MPa, the water permeability coefficient is 0.97mm / s, and the strength index does not meet the design requirements; at the same time, the permeable concrete test block shows slurry destruction, while the aggregate remains intact and in good condition, indicating that the slurry strength does not match the aggregate strength, resulting in insufficient strength of the permeable concrete.

[0102] Example 5 further proves the effectiveness of this design method in meeting the design strength and permeability coefficient of permeable concrete, and proves that when the slurry strength σ浆 When ' is greater than and close to the minimum paste strength calculated by this method, σ 浆 , the slurry strength matches the aggregate strength, and the slurry strength is fully utilized; Comparative Examples 5 to 6 show that the slurry strength is less than σ 浆 When the concrete strength is insufficient, the paste strength is greater than σ 浆 , the utilization rate of slurry strength is insufficient.

[0103] Table 3 Raw material parameters and mix ratios of Example 5 and Comparative Examples 5 to 6

Claims

1. A permeable concrete design method capable of fully utilizing material properties, characterized by: The following steps are involved: Step 1: Determine the design compressive strength σ of permeable concrete T and the design permeability coefficient k, and by the relationship P = 0.0539e 1.2181k The design porosity P of permeable concrete is calculated. Step 2: Calculate the minimum paste thickness t required for permeable concrete. The measured radius R of the aggregate and the designed porosity P are used through the relationship: The minimum slurry thickness t is calculated; where α is the equivalent coefficient for porosity calculation, and single-size aggregate is used. When the aggregate sizes are 3-5mm, 5-10mm, and 10-16mm, the values ​​of σ are 4.5, 3.3, and 2.6, respectively. Step 3: Calculate the minimum aggregate strength σ required for permeable concrete 骨 and minimum paste strength σ 浆 . The design strength of permeable concrete is σ T And the design porosity P is expressed by the relationship: Calculate the aggregate design strength σ 骨 ; Then by σ 骨 , R and t through the relationship: The calculated slurry design strength σ 浆 ; Wherein γ and μ are the equivalent coefficients of aggregate strength calculation, paste strength calculation and paste calculation radius respectively, the equivalent coefficient γ = 0.12, μ = 0.

7. Step 4: Calculation of the mix proportion of permeable concrete and selection of materials. Determine the size of the selected single-diameter aggregate and calculate the amount of aggregate based on the compact packing density of the aggregate; calculate the amount of slurry based on the aggregate surface area and the minimum slurry thickness t calculated in step 2. The mix proportion of permeable concrete can be determined based on the aggregate amount and slurry amount. Among them, the material selection should meet the actual measured strength σ of the selected aggregate 骨 ′ is not less than the minimum aggregate strength σ 骨 , and under the principle of making full use of material properties, σ 骨 ′ value should be close to σ 骨 The prepared cement paste 28d measured strength σ 浆 ′ should not be less than the minimum paste strength σ 浆 , and under the principle of making full use of material properties, σ 浆 ′ value should be close to σ 浆 Better.

2. A permeable concrete design method capable of fully utilizing material properties according to claim 1, characterized in that: The relationship in step 2 is established by the geometric relationship of the pores, specifically: in the plane single layer arrangement state, the total pore area S in the plane of the cube with a side length of a is a The standard pore area S of u planes ps and v plane edge pore areas S pe Composed of; said u=2N c 2 (pcs), v = N c -1(pcs), then S a =2N c 2 S ps +(N c -1)S pe ; According to the relationship between the porosity of permeable concrete P = α S a / a 2 , then we get The plane standard pore area S ps Satisfies the geometric relationship with R and t: The plane edge pore area S pe Satisfies geometric relationship with R: S pe =0.4292R 2 ; said N c is the aggregate calculation number, N c Satisfies the relationship with R and a: In summary, the relationship between the design porosity P of permeable concrete, the design radius R of aggregate, and the minimum paste thickness t can be obtained:

3. A permeable concrete design method capable of fully utilizing material properties according to claim 1, characterized in that: In step 3, σ 骨 With σ T The relationship between , P is obtained by converting the strength formula, specifically: under the action of the same axial force F, the design compressive strength σ of the permeable concrete is T (cube with side length a) is converted to the aggregate stress per unit area minus the void area (i.e. the minimum aggregate strength σ 骨 ), that is, σ 骨 (1-P)a 2 =F=σ T δa 2 ; The δ is the area conversion coefficient related to P, δ = 70.83P-1.9505; In summary, establish σ 骨 The relationship between σT and P is:

4. A permeable concrete design method capable of fully utilizing material properties according to claim 1, characterized in that: In step 3, σ 浆 With σ 骨 The relationship is obtained by converting the strength formula under the principle of making full use of material properties, that is, under the action of the same axial force F′, the minimum aggregate strength σ is converted by the strength formula. 骨 Converted to the minimum paste strength σ related to R and t 浆 , specifically: 浆 S 浆 =F′=σ 骨 S 骨 ; The S 骨 The effective cross-sectional area of ​​aggregate is: S 骨 =πR 2 The S slurry is the effective calculated cross-sectional area of ​​the slurry "connector" on the section perpendicular to the line connecting the centroids of the connected aggregates, specifically S 浆 =πr 2 ; The r is the radius of the slurry "connector", specifically: In summary, we establish σ 浆 With σ 骨 , R, t: Among them, γ and μ are equivalent coefficients, γ=0.12, μ=0.

7.

5. A permeable concrete design method capable of fully utilizing material properties according to claim 1, characterized in that: The aggregate types described in step 1 include multiple types of rock stone aggregates with single particle size grading of 3-5 mm, 5-10 mm, and 10-16 mm, and the components of the slurry include but are not limited to cement-based cementitious materials.

6. A permeable concrete design method capable of fully utilizing material properties according to claim 1, characterized in that: The calculated results of minimum paste thickness t and minimum aggregate strength σ 骨 , minimum paste strength σ 浆 It serves as a controlling indicator for the preparation of slurry and selection of aggregate types in the production of permeable concrete.